The Use of Gist Strategy on Students’ Achievement in Reading Comprehension at SMA Gajah Mada 3 Palembang - Husni, Na'imatul (Enrich: Jurnal Pendidikan, Bahasa, Sastra dan Linguistik, 2023)
The background of this research was the lack of students' reading skills, especially in the method they use, so that many students were only able to read with one reading style for all discourses. The result of these conditions that students' reading ability and interest in reading are still low. This study aims to determine the level of effectiveness of the experience-oriented GIST strategy in learning reading comprehension. This research used a quantitative method in the form of an experimental method with a pretest-posttest research design. The theory underlying this research was the GIST strategy. Experience-oriented learning and reading comprehension. The data from this study were in the form of test results for students in the experimental class and control class before and after being given treatment in the form of objective text with 30 questions for the pretest and 30 questions for the post test. Based on the research data collected, the results of this study indicate that using the GIST strategy was effective in teaching reading comprehension